Controlling Helix Handedness in Water‐Soluble Quinoline Oligoamide Foldamers (Eur. J. Org. Chem. 20/2014). Issue 20 (July 2014) - Dawson, Simon J.; Mészáros, Ádám; Pethő, Lilla; Colombo, Cinzia; Csékei, Márton; Kotschy, András; Huc, Ivan
Abstract : The cover picture shows a graphical representation of water‐soluble aromatic oligoamide foldamers frozen into ice cubes. This illustrates that P helices (blue) and M helices (red) are kinetically locked in water, allowing their separation as diastereoisomers by the incorporation of a chiral end group at the C terminus. Details are discussed in the article by A. Kotschy, I. Huc et al. onp. 4265 ff. The cover was designed by Dr. Simon Dawson, who is also the first author of the article.